2019
DOI: 10.1029/2018je005780
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Contribution to Ceres' Exosphere From Observed Surface Ice and Postulated Ice‐Exposing Impacts

Abstract: Telescopic observations have detected an exosphere around Ceres, composed of either water vapor or its photolytic products. Proposed mechanisms for its formation include sublimation or sputtering from solar energetic particles of buried ice, surface ice, or an optically thin seasonal polar cap. We estimate the amount of water vapor produced by known exposures of water ice, detected in Dawn spacecraft image and spectral data and by ice exposures from subresolution impact craters. We use thermal and sublimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…While the composition of the melted material is different (water ice versus silicate rock), Occator’s lobate material is the Cerean equivalent of crater-fill impact melt rocks and melt-bearing breccias found in the floors of impact craters throughout the inner solar system 22 . The now-solidified lobate material is comparatively rich in water ice when compared with the surrounding terrain 23 , and is covered by a desiccated sublimation lag most likely 1-m thick 24 . Hydrated salts are more stable than water ice at the same depth, and would stay hydrated in the presence of water ice 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…While the composition of the melted material is different (water ice versus silicate rock), Occator’s lobate material is the Cerean equivalent of crater-fill impact melt rocks and melt-bearing breccias found in the floors of impact craters throughout the inner solar system 22 . The now-solidified lobate material is comparatively rich in water ice when compared with the surrounding terrain 23 , and is covered by a desiccated sublimation lag most likely 1-m thick 24 . Hydrated salts are more stable than water ice at the same depth, and would stay hydrated in the presence of water ice 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the cases of non-detection of water-group species are just as numerous (Rousselot et al 2011(Rousselot et al , 2019Roth et al 2016;Roth 2018). Right now there is no clear explanation for the origin of Ceres' transient exosphere: sublimation rates from the known distribution of surface ice patches is two orders of magnitude lower than the water production rate derived from the observations (Landis et al 2019). Villarreal et al (2017) showed a correlation with solar energetic particle events, but ion sputtering is not effective enough (Küppers 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Small grain sizes can act as a strong barrier to vapor diffusion, and quantitative estimates place the grain size at one micron to be consistent with the low rate of vapor diffusion (Prettyman et al 2017;). The GRaND measurements, combined with models, suggest that the equatorial regions are ice-free to at least 1 m depth whereas the polar regions may have ice even at cm depth (Schorghofer 2016;Prettyman et al 2017;Landis et al 2017Landis et al , 2019.…”
Section: Ice Reservoirsmentioning
confidence: 96%